2012
DOI: 10.1016/j.mvr.2011.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyalkenals and oxidized phospholipids modulation of endothelial cytoskeleton, focal adhesion and adherens junction proteins in regulating endothelial barrier function

Abstract: Lipid peroxidation of polyunsaturated fatty acids generates bioactive aldehydes, which exhibit pro- and anti-inflammatory effects in cells and tissues. Accumulating evidence indicates that 4-hydroxynonenal (4-HNE), a major aldehyde derived from lipid peroxidation of n-6 polyunsaturated fatty acids trigger signals that modulates focal adhesion and adherens junction proteins thereby inducing endothelial barrier dysfunction. Similarly, oxidized phospholipids (Ox-PLs) generated by lipid peroxidation of phospholipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 133 publications
1
29
0
Order By: Relevance
“…4-HNE can bind to thiol (SH) and amino (NH2) groups of cysteine, lysine and histidine residues by Michael addition reaction and form a covalent bond between 4-HNE and the amino acid (Usatyuk and Natarajan, 2012). Thus, 4-HNE can increase the oxidative post translational modification (PTM) and alter the function of protein.…”
Section: Discussionmentioning
confidence: 99%
“…4-HNE can bind to thiol (SH) and amino (NH2) groups of cysteine, lysine and histidine residues by Michael addition reaction and form a covalent bond between 4-HNE and the amino acid (Usatyuk and Natarajan, 2012). Thus, 4-HNE can increase the oxidative post translational modification (PTM) and alter the function of protein.…”
Section: Discussionmentioning
confidence: 99%
“…The brain is particularly vulnerable to oxidation damage due to: i) elevated use of oxygen; ii) low antioxidant levels; and iii) high phospholipid levels. Peroxidation of membrane lipids results in the generation of oxidized phospholipids (Ox-PL) and reactive aldehydes which may increase blood-brain barrier permeability [7,8]. Recent studies have also shown that Ox-PLs induce monocyte binding to endothelial cells [8].…”
mentioning
confidence: 99%
“…Peroxidation of membrane lipids results in the generation of oxidized phospholipids (Ox-PL) and reactive aldehydes which may increase blood-brain barrier permeability [7,8]. Recent studies have also shown that Ox-PLs induce monocyte binding to endothelial cells [8].A number of mechanisms are thought to be involved in the demyelination and neurodegeneration characteristic of MS. Recently, oxidative damage has been associated with mitochondrial injury and energy failure, which may account for certain pathological features of multiple sclerosis, including demyelination, oligodendrocyte apoptosis and astrocyte dysfunction [9].…”
mentioning
confidence: 99%
“…The progressive accumulation of these adducts alters normal cell functions, and may lead to cell death [104,[109][110][111]. Nonetheless, at low and noncytotoxic concentrations, these molecules can act as second messengers in signal transduction in physiological and/or pathophysiological conditions [111][112][113][114][115].…”
Section: Peroxidation Of N-3mentioning
confidence: 99%
“…HNE can directly impair the barrier function of the endothelium by increasing its permeability [115]: it may induce changes in cellular thiol redox status, thus perturbing cell signaling pathways and leading to endothelial barrier dysfunction. Following induction of ROS, HNE may affect EC permeability, modulating cell-cell adhesion by suppressing focal adhesion kinase (FAK) phosphorylation, which in turn affects focal adhesion, adherence, and tight junction proteins, as well as integrins, which are natural FAK receptors [121].…”
Section: Hne-induced Endothelial Dysfunction and Foam Cell Formationmentioning
confidence: 99%